Quants and Poets: Advancing Methods and Methodologies in Business and Society Research. Issue 1 (January 2018) - Crane, Andrew; Henriques, Irene; Husted, Bryan W.
Business and society research has increasingly moved from the margins to the mainstream. Although this progression has benefited from advances in empirical research, the field continues to suffer from considerable methodological challenges that hamper its development. In this introductory article to the special issue, we review how far our field has come in advancing methods and methodologies in business and society research. We also highlight the methods and methodologies covered by the contributors to this special issue and how they help address key shortcomings in our field. Finally, we suggest some promising research methodologies that can address important business and society research challenges going forward.